COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING IN RANGKAH KIDUL VILLAGE, SIDOARJO DISTRICT, SIDOARJO REGENCY - Nisa, Choirun; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze community participation in the Development Planning Deliberation (Musrenbang) in Rangkah Kidul Village, Sidoarjo District, with a focus on its influence on the quality of village development. Method: Using qualitative methods, data was collected through in-depth interviews with informants such as the Village Head, members of the Village Consultative Body (BPD), and active community participants, as well as through observation and documentation. Results: Using qualitative methods, data was collected through in-depth interviews with informants such as the Village Head, members of the Village Consultative Body (BPD), and active community participants, as well as through observation and documentation. Novelty: This study provides new insights into the importance of effective communication between village governments and communities to increase participation, and recommends the need for improvements in the socialization and access to information regarding the Musrenbang process, so that development can be more responsive to local needs and community aspirations.